2022
DOI: 10.1109/tie.2021.3112964
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Performance of a Flyable Flapping Wing Rotor With Passive Pitching Angle Variation

Abstract: The present work was based on an experimental study on the aerodynamic performance of a flapping wing rotor (FWR) and enhancement by passive pitching angle variation (PPAV) associated with powered flapping motion. The PPAV (in this study 10 o ~50 o ) was realized by a specially designed sleeve-pin unit as part of a U-shape flapping mechanism. Through experiment and analysis, it was found that the average lift produced by an FWR of PPAV was >100% higher than the baseline model, the same FWR of a constant pitchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In Cases 3 (φ ∈ [−50, 20]), the linear relationship only stands when the input voltage is over 4.5 V. From the weight parameters listed in Table 1, it is found that the FWR weighs 0.187 N while the maximum average lift (0.201 N) is achieved in Case 1-8 according to Figure 11. In this case, the lift-to-weight ratio reaches 1.07 and the take-off test is conducted in our previous study [29]. During the take-off test, a 4 g wire was used to connect an external power supply to the FWR model (not taking into account the battery weight).…”
Section: The Effect Of Asymmetric Stroke Angles On the Average Lift G...mentioning
confidence: 99%
“…In Cases 3 (φ ∈ [−50, 20]), the linear relationship only stands when the input voltage is over 4.5 V. From the weight parameters listed in Table 1, it is found that the FWR weighs 0.187 N while the maximum average lift (0.201 N) is achieved in Case 1-8 according to Figure 11. In this case, the lift-to-weight ratio reaches 1.07 and the take-off test is conducted in our previous study [29]. During the take-off test, a 4 g wire was used to connect an external power supply to the FWR model (not taking into account the battery weight).…”
Section: The Effect Of Asymmetric Stroke Angles On the Average Lift G...mentioning
confidence: 99%
“…Recently, a new biomimetic layout of MAVs called a flapping wing rotorcraft (FWR) was proposed, and it has been proved to achieve higher lift and aerodynamic efficiency at low Reynolds number [5][6][7][8]. Compared with existing flapping wing robots [9][10][11], the wing is not installed symmetrically with respect to the horizontal plane but has an initial installation angle (similar to the collective angle) as shown in figure 1(A).…”
Section: Introductionmentioning
confidence: 99%
“…To date, most of the proposed FWRs [8,[19][20][21] still contain complex mechanical transmission structures, which strictly confine the wing's otherwise freely variable flapping trajectory, and further limit the aerodynamic optimization and controller design of FWRs. Furthermore, since the flapping wing part only provides an upward force without control torques, it also needs adjunct control surfaces powered by actuators that are cumbrous to stabilize.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, a new type of flapping-wing aircraft-micro Flapping Wing Rotorcrafts (FWRs)-integrates both the advantages of flapping and rotary wings, demonstrating superior capability of lift generation [1]. The state-of-the-art microFWRs even showcase several millimeter/milligram-scale designs [1,9,[12][13][14][15][16][17][18][19] that have rarely been achieved by conventional fixed or rotary-winged vehicles. Such microFWRs are foreseen as alternatives to commercial drones and would be in used in increasing breadths of applications such as search and rescue, surveying and inspection, and aerial photography [20].…”
Section: Introductionmentioning
confidence: 99%